Pengaruh Penggunaan Youtube Terhadap Kemampuan Literasi Numerasi Pada Anak Usia Dini Kelompok B - Icam Sutisna; Waode Eti Hardiyanti; Resti Retno Sari (Student Journal of Early Childhood Education, 2023)
The study findings revealed that a sample size of 20 children indicated a significant difference in the average scores between the pretest and posttest of numeracy literacy skills. This indicated an influence of YouTube usage in enhancing the children's early numeracy literacy skills. The statistical analysis of the pretest scores revealed that the initial numeracy literacy ability was 19.1 (19.1%) of the total score, which amounted to 8. The posttest value of children's numeracy literacy results in an average score of 28.25 (28.25%) of a total score of 8, with the one-sample Kolmogorov-Smirnov test data normality test with a pretest significance value of 0.099 > 0.05, and a posttest significance value of 0.200 > 0.05, and the results of the t-test obtained a value of ￼ 23.719, while the value of at (x) = 0.05 is 2.093 if 23.719 > 2.093, then Ho is rejected, and Ha is accepted. Meaning that there is an influence of the use of YouTube media on numeracy literacy skills in group B early childhood at TK State Pembina Botumoito Kindergarten. The utilization of YouTube as an alternative solution is suggested to address the challenges faced by learners. The study findings revealed that a sample size of 20 children indicated a significant difference in the average scores between the pretest and posttest of numeracy literacy skills. This indicated an influence of YouTube usage in enhancing the children's early numeracy literacy skills. The statistical analysis of the pretest scores revealed that the initial numeracy literacy ability was 19.1 (19.1%) of the total score, which amounted to 8. The posttest value of children's numeracy literacy results in an average score of 28.25 (28.25%) of a total score of 8, with the one-sample Kolmogorov-Smirnov test data normality test with a pretest significance value of 0.099 > 0.05, and a posttest significance value of 0.200 > 0.05, and the results of the t-test obtained a value of ￼ 23.719, while the value of at (x) = 0.05 is 2.093 if 23.719 > 2.093, then Ho is rejected, and Ha is accepted. Meaning that there is an influence of the use of YouTube media on numeracy literacy skills in group B early childhood at TK State Pembina Botumoito Kindergarten. The utilization of YouTube as an alternative solution is suggested to address the challenges faced by learners.